Peanut Variety Protection - Elmo B. Whitty (EDIS)
This document is SS-AGR-186, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November 2002.